The Impact of Mobile Telephone Use on Economic Development of Households in Uganda - Sanne Lise Blauw; Philip Hans Franses (Tinbergen Institute, 2011)
We examine the impact of mobile telephone use on economic development of individual households. Unique cross-sectional data were collected in personal interviews with heads of households (N=196) in Uganda. Economic development is measured at the household level by the Progress out of Poverty Index. We find strong support that mobile phone use positively impacts economic development.
urn:NBN:nl:ui:15-1765/26793
Keywords: I3; 330; Economic development; Progress out of poverty index; mobile telephone; mobile banking; mobile search